2023
DOI: 10.3389/fphar.2022.1090955
|View full text |Cite
|
Sign up to set email alerts
|

Bear bile powder ameliorates type 2 diabetes via modulation of metabolic profiles, gut microbiota, and metabolites

Abstract: Introduction: Bear bile powder (BBP) is widely used in the clinic and has a hypoglycemic effect, but its mechanism is not clear.Methods: In this study, type 2 diabetes mellitus (T2DM) rats induced by a high-sugar and high-fat diet combined with streptozotocin were given BBP, and biochemical indexes, pathological sections, metabonomics, intestinal microbiota (IM) and short-chain fatty acids (SCFAs) were determined.Results: The results showed that BBP could reduce blood glucose, relieve inflammation, insulin res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…On the other hand, there was an enrichment of the f-Lactobacillaceae ( g-Lactobacillus and g-Limosilactobacillus ), f-Erysipelotrichaceae ( g-Dubosiella ), and f-Lachnospiraceae ( Lachnospiraceae_NK4A136_group ) in the control obese mice compared to ACE2-overexpressed mice. This is consistent with findings in the T2DM cohort and mice, suggesting a positive correlation between these species and blood glucose levels, liver injury, lipid metabolism, and ROS ( Karlsson et al., 2013 ; Wang et al., 2020 ; Chen et al., 2023 ). However, the function of these bacteria may not be constant.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, there was an enrichment of the f-Lactobacillaceae ( g-Lactobacillus and g-Limosilactobacillus ), f-Erysipelotrichaceae ( g-Dubosiella ), and f-Lachnospiraceae ( Lachnospiraceae_NK4A136_group ) in the control obese mice compared to ACE2-overexpressed mice. This is consistent with findings in the T2DM cohort and mice, suggesting a positive correlation between these species and blood glucose levels, liver injury, lipid metabolism, and ROS ( Karlsson et al., 2013 ; Wang et al., 2020 ; Chen et al., 2023 ). However, the function of these bacteria may not be constant.…”
Section: Discussionsupporting
confidence: 91%
“…Among them, Butyricicoccus , B. porcorum , and F. prausnitzii have been proven to be beneficial bacteria, promoting improvement in T2DM ( Heinken et al, 2014 ; Xu et al, 2015 ). Additionally, Allobaculum and Bacteroides have been demonstrated to be harmful bacteria, detrimental to the treatment of T2DM ( Wang et al, 2020 ; Chen et al, 2023 ). Notably, some bacteria such as Streptococcus and Bacteroides are closely associated with BAs metabolism, indicating that JNDX may further influence BAs profile in T2DM rats.…”
Section: Resultsmentioning
confidence: 99%
“…Bacteroides enterotype is an independent risk factor for T2DM, which attributes to elevated LPS levels leading to diminished insulin sensitivity ( Wang et al, 2020 ). Allobaculum has been shown to produce trimethylamine oxide, which can not only promote fat production by inhibiting the BA-mediated hepatic FXR signaling, but also induce insulin resistance, thus impacting blood glucose homeostasis and the occurrence and development of T2DM ( Chen et al, 2023 ). Furthermore, Streptococcus thermophilus MN-ZLW-002 regulates gut microbiota by adjusting the composition of BAs and reduces the levels of high lipid and glucose.…”
Section: Discussionmentioning
confidence: 99%
“…Jeotgalicoccus had a positive correlation with acetate, propionate and butyrate after soy isoflavone feeding in mice ( 68 ). More studies have also found that other taxa, such as Gemella ( 69 ), Odoribacter ( 70 ), and Tyzzerella ( 71 ), have the ability to produce SCFAs. However, as the potential SCFAs-producing species were only identified by statistical analysis in this study, further validation by deep genomic analysis combined with wet-experiments is required due to the limited sample size and low-resolution species identification of amplicon sequencing.…”
Section: Discussionmentioning
confidence: 99%